Retraction Note: PPP1, a plant-specific regulator of transcription controls Arabidopsis development and PIN expression - René Benjamins (Nature Portfolio, 2021)
Editor's Note: this Article has been retracted; the Retraction Note is available at https://doi.org/10.1038/s41598-021-87406-5 .